Single‐cell transcriptional profiling of human carotid plaques reveals a subpopulation of endothelial cells associated with stroke incidences. Issue 12 (8th May 2022) - Li, Fengchan; Du, Yun; Hong, Lei; Liu, Ziting; Yan, Kunmin; Liu, Chu; Zhu, Zhen; Lu, Qiongyu; Tang, Chaojun; Zhu, Li
Abstract: The differences in plaque histology between symptomatic and asymptomatic patients have been widely accepted. Whether there is a heterogeneity of cells between symptomatic and asymptomatic plaques remains largely unclear. To reveal the potential heterogeneity within different plaques, which may contribute to different stroke incidences, we obtained the scRNA‐seq data from symptomatic and asymptomatic patients and identified eight cell types present in plaques. Further analysis of endothelial cells (ECs) revealed three distinct EC subpopulations appeared to be endowed with specific biological functions such as antigen processing and presentation, cell adhesion, and smooth muscle cell proliferation. Of note, the differentially expressed genes of the EC 2 subpopulation showed that the genes involved in cell adhesion were up‐regulated in asymptomatic plaques compared to symptomatic plaques. Integrating the data of intraplaque haemorrhage and plaque stability, the 5th top‐enriched biological process was cell adhesion in the stable or non‐haemorrhaged plaques compared to unstable plaques or haemorrhaged plaques. Among these cell adhesion‐related genes, the intersection gene AOC3 may play a vital role in plaque haemorrhage and plaque stability. Targeting cell adhesion and the specialized genes may provide potential new therapeutic directions to prevent asymptomatic patients from stroke.